Preliminary results of some forage legume populations cultivated in three different Sardinian environments - Vargiu M.; Spanu E.; Loche F.; Salis L. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
After several years of characterization and evaluation of numerous annual legume populations collected in different areas in Sardinia, further studies in different environments were necessary to confirm the preliminary results obtained in the experimental farm of Ussana. Ten populations of Trifolium subterraneum and Medicago spp. annual legumes were tested in field plots and in three different environments characterized by different soil-types and altitude. Preliminary data about adaptability, forage and seed production in the first year are given in this paper. Conclusions can not be drawn and other studies are necessary to confirm the agronomic value of the tested populations.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)